IMPROVING THE RESULTS OF MATH LEARNING THROUGH SCRAMBLE COOPERATIVE MODEL WITH THE APPROACH OF CONTEXTUAL TEACHING AND LEARNING MODEL - Ahmad Rustam; Muhammad Adli (Universitas Sembilanbelas November Kolaka, 2016)
This research is motivated by the desire of the author to enhance students' skills and learning design that is not centered on the teacher. Thus, this study aims to improve students' mathematics learning outcomes through Scramble Cooperative Learning Model with Contextual Teaching and Learning (CTL) Approach at the class VIIIB SMP Negeri 1 Latambaga. The study was conducted on 28 April 2015 s / d dated May 28, 2015. The subject of this research is class student of SMP Negeri 1 Latambaga VIIIB. This research is a Classroom Action Research conducted in two cycles with study procedures: (a) Conducting planning to implement the learning process, (b) Implement the action in accordance with the plan, (c) Conducting observations of students and teachers during the process of the action takes place, (d) Conducting evaluations / tests to students in each end of the cycle, (e) to reflect and analyze the shortcomings and weaknesses during the first cycle for the plan of action on the second cycle. The results obtained are in action first cycle, the learning outcomes of students increased from an average score of initial tests before action is 68.25 into 77.71 or 78.12% with the percentage of completeness that 25 of the 32 students received grades ≥75, it this has not shown success according to defined indicators of success. In the second cycle of the results obtained are as many as 27 students get value ≥75 with an average value of 83.15 or with a percentage of 84.37%. This means that the results of the research for cycle I and cycle II. It can be concluded that the results students grade VIIIB of SMP Negeri 1 Latambaga on material geometry through cooperative learning model scramble with CTL approach that took effect on improvement of learning outcomes.